Hepatoprotective activity of depsidone enriched Cladonia rangiferina extract against alcohol-induced hepatotoxicity targeting cytochrome P450 2E1 induced oxidative damage - Ila Shukla; Lubna Azmi; Ch. V. Rao; Talha Jawaid; Mehnaz Kamal; Amani S. Awaad; Saleh I. Alqasoumi; Osama A. Alkhamees; Saud M. Alsanad (Elsevier, 2020)
Alcoholic liver disease (ALD) is a broad-spectrum disorder, covering fatty liver, cirrhosis, alcoholic hepatitis and in extreme untreated condition hepatocellular carcinoma (HCC) may also develop. Cladonia rangiferina (CR) is a class of lichen having a broad spectrum of pharmacological activity. It is used like traditional natural sources in ancient times in India, China, Sri Lanka, etc. Folkloric record about CR has reported their use as an antimicrobial, antitumor, antioxidant, anti-inflammatory activities, etc. Hence, the present study was requested to ascertain the effect of the ethanolic extract of Cladonia rangiferina (CRE) on alcohol-induced hepatotoxicity. The animals were evaluated for the estimation of the liver in vivo biochemical antioxidant parameters. The liver tissues were further evaluated histopathologically and western blotting examination for localization of apoptotic gene expression that plays a pivotal role in hepatotoxicity. The results of this study reveal that CRE proves to be helpful in the treatment of alcohol-induced hepatotoxicity and oxidative stress. Results of different markers have shown that among all, CRE has demonstrated the best hepatoprotective activity. These observations say about the importance of the components of the extract. The ameliorative action of CRE in alcoholic liver damage may exist due to antioxidant, anti-inflammatory, and anti-apoptotic activities. Keywords: Hepatotoxicity, Cladonia rangiferina, Inflammation, Apoptosis